Child labor in the mines in Calabria Bourbons between old rules and new "rights" (Italian Review of Legal History, 2019)
The exploitation of children employed in the narrow tunnels of the underground from which they extract the minerals used by big industry, has always been a bitter chapter in the debate on labor protection. The use of minors in jobs not suitable for their age and, in any case, in the absence of rules or in spite of laws that repress abuses, is still a drama lived in many countries, as can be seen every day from various investigations in the past few years .Special attention has been the subject of especially the use of children in the mines from which are extracted materials, such as coltan, widely used in high-tech. The scenario is often devastating, revealing the inhuman conditions in both high rate of industrialization countries, like China, it is in the poorest Third World countries like Congo.Starting from 1861, in the newly unified, the problem of child labor was not directly addressed, but it poses a corollary in the parliamentary debate that concentrated his efforts in 'unify the laws in force in the former pre-unification States on the subject of mines , quarries and peat bogs, configuring a valid owner regime for the entire country (usque domain to inferos or res nullius). The capitalist option, which ultimately prevailed, did not show, for obvious reasons, great enthusiasm towards the introduction of a labor discipline, setting limits and prohibitions in the employment relationship, it would limit the advantage for the company to avail itself of "human material" cheap (and these were especially child laborers).In 1876 the parliamentary inquiry conducted by deputies Franchetti and Sonnino, he raised the matter of the cd. carusi, just under 7-8 years of age used as laborers in the Sicilian sulfur mines. The country took note of urgency to regulate this matter, even under the pressure of trade union movements that were born in those years, but the journey was still long. Ten years later, the law Berti in 1886 established some important principles, such as the minimum age for access to employment or the hourly limit; However, the legislation was in fact not implemented and it was not until the new law, given by the Minister Carcano made in 1902 to see the first forms of protection for child workers.If this is the normative horizon within which unfolds the story of child labor discipline in Italy, it may seem surprising that already in 1845 in a remote mining village of Calabria, Pazzano, the iron mining activities, which fed the Regie workshops Mongiana, the largest iron and steel industry of the Italian peninsula before the unification of the country, the organization of work in the mine was fully translated into specific regulations, which set the minimum age of 14 years for access to work, limited to eight hours working day, excluded child laborers from hazardous or heavy activities considered.The Regulation for the iron mines of the Royal factories Mongiana, inspired by the military logic Bourbon who directed and coordinated the organization of the production cycle in the great state of flourishing industry made in the thirties of the '800, however, not imposed rules contrary to the character of the population, but was grafted into existing traditions, harmonizing with this culture in that territory: a strongly influenced by Byzantine spirituality of hermit monks culture, which for centuries roamed the "Sacred Valley", inculcating in far removed from the logic customs and mentality populations profit; a culture that helped the people to have early awareness of the importance of respecting the territory, using its resources in a balanced way, respecting the same, Certainly, this lifestyle difficult to reconcile with the capitalist model, the liberal bourgeois Italy was trying to accomplish, with whom, in fact, immediately entered into conflict. The closure of the plants, which in 1876 was sold at public auction together with the whole compendium of goods entering the production cycle of the company (forests, forests, mines), led the massive emigration and depopulation of the territory.     The story of the Calabrian mines, in addition to returning the image of an industrious and hard-working land, to which he emigrated in search of work, you can discover unpublished pages of the history of child labor, which in advanced exploitation tips contrasted experiences and correct disciplined organization.
Keywords: Mines; Minors; Steelworking; Calabria; Byzantines